2000
DOI: 10.1038/sj.bmt.1702189
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol selectively inhibits leukemia cells: a prospective agent for ex vivo bone marrow purging

Abstract: Summary:Ex vivo purging of contaminating tumor cells may reduce the incidence of relapse in patients undergoing bone marrow transplantation. In this study we demonstrate that resveratrol, a phytoalexin with anti-oxidant and chemopreventive activity, exhibits anti-leukemic activity against mouse (32Dp210, L1210) and human (U937, HL-60) leukemic cell lines by inhibiting cell proliferation. Long-term exposure to resveratrol also inhibits the clonal growth of normal hematopoietic progenitor cells but at a higher I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 20 publications
4
66
0
1
Order By: Relevance
“…22 Furthermore, mouse and human leukemic cells selectively undergo apoptosis under resveratrol, while hematopoietic progenitor cells and differentiated cells are largely resistant. 20,23 However, different cell types and even the same cell lines have produced conflicting results with regard to the effects of resveratrol. In the human HL60 promyelocytic leukemia cell line, the drug has been variably reported to induce apoptosis, 24 differentiation 2 and differentiation with S/G 2 arrest without apoptosis.…”
Section: Epithelial Differentiation At Early Times During Resveratrolmentioning
confidence: 99%
“…22 Furthermore, mouse and human leukemic cells selectively undergo apoptosis under resveratrol, while hematopoietic progenitor cells and differentiated cells are largely resistant. 20,23 However, different cell types and even the same cell lines have produced conflicting results with regard to the effects of resveratrol. In the human HL60 promyelocytic leukemia cell line, the drug has been variably reported to induce apoptosis, 24 differentiation 2 and differentiation with S/G 2 arrest without apoptosis.…”
Section: Epithelial Differentiation At Early Times During Resveratrolmentioning
confidence: 99%
“…However, it still has its limitation of high relapse rate, as compared with Allo-HSCT and the limitation is ascribed to the risk of reinfusing residual leukemic cells at the time of harvest. [5][6][7] Several studies on animals have indicated that it is necessary to purge leukemic cells from the bone marrow ex vivo prior to transplantation. [8][9][10][11][12] Therefore, it is essential to eradicate selectively the leukemic cells from grafts for the application of auto-HSCT in leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has recently attracted considerable interest because of its inhibitor activity on multiple cellular events associated with carcinogenesis (Jang et al, 1997;Runqing et al, 1999). Resveratrol has been shown to have potent growth inhibitory effects on various cancer cells such as colonic tumor cells (Schneider et al, 2000), leukemic cells (Gautam et al, 2000;Dorrie et al, 2001), breast and prostate cancer cells (Mitchell et al, 1999;Damianaki et al, 2000), and has been suggested as one of the most promising cancer chemopreventive agents.…”
mentioning
confidence: 99%